Hydrocobaltierung von 1,3-Dihydro-1,3-diborafulven-Derivaten HCo(CO)4: Herrn Prof. Dr. Paul Binger zum 60. Geburtstag gewidmet = Hydrocobaltation of 1,3-dihydro-1,3-diborafulvene derivatives with HCo(CO)4 - Nagy-Magos, Zsuzsa; Enders, Markus; Pritzkow, Hans; Siebert, Walter (Zeitschrift für Naturforschung. B, a journal of chemical sciences, 1992)
(3) Hydrocobaltation reactions of 1,3-dibora-4,5-benzofulvene (2) and 1,3-dibora[5]radialene with HCo(CO) 4 lead to the complexes tricarbonyl-(η 5 -4,5-benzo-2-isopropyl-1,3-dimethyl- 2,3-dihydro-1,3-diborolyl)cobalt (4) and tricarbonyl-(η 5 -isopropenyl-2,5-diisopropyl-1,3-dimethyl-1,3-dihydro-1,3-diborolyl)cobalt (5) in 24% and 5% yield, respectively. The constitution of 4 and 5 follows from the spectroscopic data, and is proven by an X-ray structure analysis of 4. The formation of 5 is accompanied by a 1,5-hydrogen shift in the 1.3-dibora[5]radialene (3).
Im Titel ist "4" im Ausdruck "HCo(CO)4" tiefgestellt
Gesehen am 09.11.2022
Keywords: Festschrift